2019
DOI: 10.1002/eat.23158
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in anorexia nervosa: Meta‐analysis and meta‐regression of cross‐sectional and longitudinal studies

Abstract: Objective Clinically, anorexia nervosa (AN) presents with altered body composition. We quantified these alterations and evaluated their relationships with metabolites and hormones in patients with AN longitudinally. Method In accordance with PRISMA guidelines, we conducted 94 meta‐analyses on 62 samples published during 1996–2019, comparing up to 2,319 pretreatment, posttreatment, and weight‐recovered female patients with AN with up to 1,879 controls. Primary outcomes were fat mass, fat‐free mass, body fat per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 115 publications
(222 reference statements)
6
36
0
Order By: Relevance
“…Similar patterns are observed in the UK and the Netherlands, where the incidence rate in females is higher than in males, with the peak incidence rate in adolescent girls [16,17]. A meta-analysis of 62 studies published from 1996 to 2019 showed that female AN patients had 50% less body fat mass than their healthy counterparts on average, with fat being stored mainly in the trunk region [18]. Body fat loss has been observed in different age groups.…”
Section: Introductionsupporting
confidence: 58%
“…Similar patterns are observed in the UK and the Netherlands, where the incidence rate in females is higher than in males, with the peak incidence rate in adolescent girls [16,17]. A meta-analysis of 62 studies published from 1996 to 2019 showed that female AN patients had 50% less body fat mass than their healthy counterparts on average, with fat being stored mainly in the trunk region [18]. Body fat loss has been observed in different age groups.…”
Section: Introductionsupporting
confidence: 58%
“…Body composition is significantly altered in AN. Accordingly, lower fat mass and fat free mass were found in patients with AN associated with an extreme physiological state including numerous endocrine and metabolic adaptions 3 , 4 . Furthermore, hematological changes and a respectively increased risk of infection seem to be associated with chronicity of AN, weight loss and the severity of underweight 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of BIA allows the monitoring of compartmental weight gain during refeeding. A recent meta-analysis by Hübel et al reported 50% less FM and 5 kg less FFM in AN patients compared to the control group [ 36 ]. Recovery was associated with restored FM primarily stored in the trunk as previously described [ 37 ], while long-term lower levels of FFM were observed compared to the control group.…”
Section: Discussionmentioning
confidence: 99%